2020
DOI: 10.1021/acs.joc.0c02637
|View full text |Cite
|
Sign up to set email alerts
|

ZnI2-Catalyzed Aminotrifluoromethylation Cyclization of Alkenes Using PhICF3Cl

Abstract: We report here an alternatively catalytic aminotrifluoromethylation of alkenes using PhICF 3 Cl as a bifunctional reagent along with ZnI 2 as a dual catalyst. A combined catalytic strategy was established for the intramolecular aminotrifluoromethylation of 4-pentenamines. As a result, a set of 2-trifluoroethyl-pyrrolidines was obtained in a high selectivity. Mechanism studies revealed that the reaction included an iodine anion-catalyzed radical chlorotrifluoromethylation of alkenes and a sequential Lewis acid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Further, cyclized product is obtained by intramolecular amination and intermolecular chlorination. On other hand, cation is regenerated by ZnCl 2 from trifluoromethylated species [59] …”
Section: Transformations Involving Hypervalent Iodine Reagents and 1s...mentioning
confidence: 99%
“…Further, cyclized product is obtained by intramolecular amination and intermolecular chlorination. On other hand, cation is regenerated by ZnCl 2 from trifluoromethylated species [59] …”
Section: Transformations Involving Hypervalent Iodine Reagents and 1s...mentioning
confidence: 99%
“…It should be mentioned that there were also some related reports on the halo-perfluoroalkylation of unsaturated bonds which just contained one example about trifluoromethylation [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ].…”
Section: Iodotrifluoroalkylationmentioning
confidence: 99%
“…Cyclofunctionalization reactions represent an important strategy for the synthesis of functionalized (hetero)cyclic structures from simple starting materials that would otherwise be difficult to prepare. 29 In this family of reactions, sulfetherification of alkenols offers a promising strategy for the selective synthesis of sulfenyl-substituted oxacycles within a single click. One of the earliest reports on the cyclizative sulfenylation of alkenols was published by Capozzi and co-workers in 1981, 30 who showed that the treatment of o -allylphenols 33 with methyl(bismethy1thio)sulfonium hexachloroantimonate 34 in the absence of any catalyst or additive in anhydrous DCM, resulted in the formation of methylthio-substituted dihydrobenzofurans 35 in good yields and selectivities ( Scheme 12a ).…”
Section: Intramolecular Alkoxysulfenylation Of C–c Double Bondsmentioning
confidence: 99%